2011
DOI: 10.1021/ja1072178
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Examination of Cu2+ Binding Structure for Amyloid Fibrils of 40-Residue Alzheimer’s β by Solid-State NMR Spectroscopy

Abstract: Cu2+ binding to Alzheimer’s β (Aβ) peptides in amyloid fibrils has attracted broad attention, as it was shown that Cu ion concentration elevates in Alzheimer’s senile plaque and such association of Aβ with Cu2+ triggers the production of neurotoxic reactive oxygen species (ROS) such as H2O2. However, detailed binding sites and binding structures of Cu2+ to Aβ are still largely unknown for Aβ fibrils or other aggregates of Aβ. In this work, we examined molecular details of Cu2+ binding to amyloid fibrils by det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
221
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(249 citation statements)
references
References 102 publications
23
221
1
Order By: Relevance
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of amyloid fibrils invoke X-ray crystallography (22)(23)(24), EM (19,25,26), and thioflavin T fluorescence (19,27), revealing the polypeptide's global behavior, whereas NMR studies provide residue-level information for the fibrils (28)(29)(30). Nevertheless, we know little about soluble Aβ aggregates owing to their intrinsically high heterogeneity.…”
mentioning
confidence: 99%
“…The assignment of the histidine aromatic carbon chemical shifts is in agreement with a recent study in which it was found that His-13, His-40 and the Val-40 carboxylic group are involved in binding to a Cu(II) metal ion. 49 Assuming that His-13 and His-14 are located in a b-sheet secondary structure element, His-14 is facing the solvent and cannot be involved in hydrogen bonds within one protofilament. The i, i À 2 and i, i + 2 neighboring residues Val-12 and Lys-16 are not potential hydrogen bonding partners.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because the Cu 21 and His residues did not interact, the results from this MD simulation contradict those reported in the literature. 9,16,17 Consequently, we evaluated the amino acid residues that interacted with Cu 21 , Asp 23, and Glu 22, as displayed in Figure 4(B-D). The distance between Cu 21 and Asp 23 was lower (2.01 Å ) compared with that between Cu 21 and Glu22 (4.81 Å ) at the end of the simulation [ Fig.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%